Young people and housing transitions during COVID-19: navigating co-residence with parents and housing autonomy. Issue 1 (1st December 2022) - Kajta, Justyna; Pustulka, Paula; Radzińska, Jowita
Abstract: Research on housing transitions consistently points out the significance of housing autonomy and stability in young adults' lives. While the pandemic has arguably exacerbated the already unfavorable conditions in the housing market (in terms of unaffordability and inaccessibility of quality dwellings), it is important to see how young people navigate the challenges of co-residing with parents, leaving home, and establishing housing autonomy, especially with regard to how housing transitions are embedded into broader processes of transitions-to-adulthood. Based on a qualitative study ( n  = 35) of young adults (ages 18–35) in Poland, the article covers the two dimensions of housing transitions in the COVID-19 era. Specifically, it accounts for the pre-pandemic housing situation (living with parents vs. housing autonomy) and the subjective housing situation during the pandemic (comfort vs. discomfort). The analysis reveals four types of (A) Appreciated nesting, (B) Burdensome nesting, (C) Consolidated autonomy, and (D) Disrupted autonomy, thus offering a new 'ABCD' typology for investigating housing transitions and housing paths during the crisis.